Prosthetic valve endocarditis caused by Pseudomonas luteola - Casalta, Jean-Paul (BioMed Central, 2005)
BACKGROUND: Pseudomonas luteola has been recognized as an uncommon cause of bacteremia and of infections in patients with underlying medical disorders CASE PRESENTATION: We isolated P. luteola from blood cutures in a patient with prosthetic valve endocarditis developed 16 months after cardiac surgery. CONCLUSION: P. luteola is a rare opportunistic agent, with a propensity of infecting valvular prostheses.